Extensive non-redundancy in a recently duplicated developmental gene family - Baker, EA; Gilbert, SPR; Shimeld, SM; Woollard, A (BMC, 2021)
BACKGROUND: It has been proposed that recently duplicated genes are more likely to be redundant with one another compared to ancient paralogues. The evolutionary logic underpinning this idea is simple, as the assumption is that recently derived paralogous genes are more similar in sequence compared to members of ancient gene families. We set out to test this idea by using molecular phylogenetics and exploiting the genetic tractability of the model nematode, Caenorhabditis elegans, in studying the nematode-specific family of Hedgehog-related genes, the Warthogs. Hedgehog is one of a handful of signal transduction pathways that underpins the development of bilaterian animals. While having lost a bona fide Hedgehog gene, most nematodes have evolved an expanded repertoire of Hedgehog-related genes, ten of which reside within the Warthog family.